De la textura psíquica a la infraestructura urbana. La visión y la distancia - Sanabria, Carolina (2012)
In the phenomenological vision, there is a tight link between the distance that separates the eye from its object. This article explains how it functions and its derivations by working on it through art-painting, movie making, and literature… that intermediate space shows a tension that becomes the branches of desire.